2017
DOI: 10.1371/journal.pone.0179426
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid, an important antioxidant contributing to survival in termites

Abstract: Reactive oxygen species (ROS) are generated spontaneously in all organisms and cause oxidative damage to biomolecules when present in excess. Accumulated oxidative damage accelerates aging; enhanced antioxidant capacity may be a positive factor for longevity. Recently, numerous studies of aging and longevity have been performed using short-lived animals, however, longevity mechanisms remain unknown. Here we show that a termite Reticulitermes speratus that is thought to be long-lived eusocial insect than other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…The connection between ATM deficiency, radiation, and metabolic alterations are well known, including direct phosphorylation of key mitochondrial proteins and reactive oxygen species (ROS) regulation following exposure to genotoxic stressors [Shiloh and Ziv, ]. Such significant metabolic alterations were also indicated in our study, with increases in metabolites such as uric acid (anti‐oxidant) from purine catabolism [Tasaki et al, ] and glutaric acid (pro‐oxidant) from fatty acid degradation [Latini et al, ].…”
Section: Discussionsupporting
confidence: 68%
“…The connection between ATM deficiency, radiation, and metabolic alterations are well known, including direct phosphorylation of key mitochondrial proteins and reactive oxygen species (ROS) regulation following exposure to genotoxic stressors [Shiloh and Ziv, ]. Such significant metabolic alterations were also indicated in our study, with increases in metabolites such as uric acid (anti‐oxidant) from purine catabolism [Tasaki et al, ] and glutaric acid (pro‐oxidant) from fatty acid degradation [Latini et al, ].…”
Section: Discussionsupporting
confidence: 68%
“…Tasaki et al. () reported that the accumulation of UA considerably increases free radical‐scavenging activity and resistance against ultraviolet‐induced oxidative stress in laboratory‐maintained termites. Moreover, Kean et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vitellogenin is known to act as an antioxidant that promotes survival in honeybee queens (Seehuus et al ., ; Corona et al ., ). Antioxidant systems are thought to be associated with termite survival and also fecundity (Tasaki, Kobayashi et al ., ; Tasaki, Sakurai et al ., ). We found that, under hypoxic conditions, queens exhibited more than five times higher expression levels of RsCAT1 at 2 weeks than at 1 day (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In A. islandica , adaptation to hypoxic conditions increases mitochondrial reactive oxygen species formation, which later induces oxidative stress under normoxia, due to a hypoxia adaptive metabolism (Strahl et al ., ). Consistent with the high sensitivity to atmospheric O 2 conditions in termites (Tasaki, Sakurai et al ., ), these findings suggest the possibility that termites have adapted for survival in hypoxic conditions. In addition, we observed that survival decreased to 25% after 20 weeks, even under hypoxic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%